Integration of Blockchain and Digital Forensics for Data Transparency and Verification : A Systematic Literature Review - Sri Nurhayati; Diana Effendi; Anggun Fergina; Irawan Afrianto; Estiko Rijanto; Irfan Dwiguna Sumitra (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2025)
Data integrity and transparency are increasingly critical concerns in the digital era. Various challenges in digital forensics arise from the growing prevalence of evidence manipulation and digital tampering, which can compromise the validity of legal investigations. This study conducts a systematic review of the potential application of blockchain technology as a solution for ensuring the authenticity and verification of digital data, employing the Systematic Literature Review (SLR) method guided by the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework. A total of 156 relevant articles sourced from the Scopus database and published between 2018 and 2025 were selected and analyzed. The results reveal a significant increase in publications since 2020, with five main research clusters identified, including the integration of Artificial Intelligence (AI) and cybersecurity. Key findings confirm that blockchain effectively functions as a trust layer, creating an immutable and transparent chain of custody. This study concludes that blockchain integration provides a strong foundation for developing more accountable, secure, and reliable digital forensic systems